La administración pública en Gran Bretaña - Plowden, William (1993)
This article focuses on the central national government of Great Britain. It outlines the most important permanent features of the British administration, those which have remained constant over the past hundred years or so. It then describes the major changes in the public service between 1960 and 1970 and during the government of Margaret Thatcher. It also discusses some unresolved issues and identifies key lessons learned on how to reform and maintain an efficient public administration. Furthermore, it is explained that the British civil service has been altered by accession to the European Community, because their laws restrict the formulation or implementation of British public policies. Finally, thirteen essential elements for an effective civil service in a modern democratic state are mentioned.